Chemical Composition and Molecular Formula of Rajmahal Bentonite (Jharkhand) - Gupta, Arushi; Kumar, Manoj; Jha, A.K.; Mishra, B.K.; Choudhary, J.; Mishra, Bivekanand (Asian Journal of Chemistry, 2011)
Twenty six samples of bentonite of Rajmahal hills (Jharkhand) were studied for their percentage composition of constituents such as SiO2, Al2O3, Fe2O3, TiO2, P2O5, Na2O, MgO, CaO and K2O. These samples were collected from different places and available in different colours from Rajmahal hills. These samples contain high percentage of silica with lower limit of 34.64 % and higher limit of 56.24 % was comparable well with the literature values. Theoretical molecular formula was calculated and presented as (SiaAlb)(AlcFedMge)CafNagKhO10(OH)2 where a = 2.57- 3.57, b = 0.42-1.43, c = 1.14-1.67, d = 0.10-0.56, e = 0.01-0.53, f = 0.03-0.48, g = 0.12-1.23 and h = 0.03-0.53. The theoretical formula of bentonite minerals of Rajmahal hills are reported for first time in literature.